2013
DOI: 10.1186/1471-2407-13-580
|View full text |Cite
|
Sign up to set email alerts
|

The anti-tumor effect of shikonin on osteosarcoma by inducing RIP1 and RIP3 dependent necroptosis

Abstract: BackgroundOsteosarcoma is the most frequent primary malignant bone tumor, notorious for its lung metastasis. Shikonin, an effective constituent extracted from Chinese medicinal herb, was demonstrated to induce necroptosis in some cancers.MethodsMTT assay was performed to detect cell survival rate in vitro. Flow cytometry was used to analyze cell cycle and cell death. Western blot was performed to determine the expression levels of RIP1, RIP3, caspase-3, caspase-6 and PARP. The tibial primary and lung metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 162 publications
(159 citation statements)
references
References 35 publications
3
153
0
3
Order By: Relevance
“…Cell cycle and apoptosis proceeded as we previously described 21. Apoptosis was detected by FCM and analysed using BD Cellquest software (BD Biosciences, San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Cell cycle and apoptosis proceeded as we previously described 21. Apoptosis was detected by FCM and analysed using BD Cellquest software (BD Biosciences, San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Shikonin has demonstrated anti-tumor potent, in which it induces cancer cell apoptosis and necroptosis [23][24][25]. Recently, we reported that high-dose of Shikonin had prompt but profound anti-tumor effect on both primary and metastatic OS, through inducing RIP1 and RIP3-dependent cancer cell necroptosis [26]. Moreover, Shikonin inhibits OS cell invasion through suppression of MMP13 [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the overexpression of anti-apoptotic proteins, many cancers have been found to develop resistance mechanisms against apoptosis-inducing chemotherapeutic agents [12][13][14]. In this regard, programmed necrosis, or type III programmed cell death, is expected to be a promising approach, and several agents have recently been found to induce necrosis as an anticancer mechanism [15][16][17][18][19]. Early-phase clinical trials for therapeutics that target regulators of necrotic cell death are under way [20].…”
Section: Introductionmentioning
confidence: 99%